Edukasi dan Pendampingan Praktik Cuci Tangan Enam Langkah pada Anak Berkebutuhan Khusus di SLB-C Tunagrahita YPPLB Makassar - Agnes Angelina Abralia Lureng; Fatma Putri Mellese; Magdalena Hope Werang; Nur Amaliah Yahya; Mikawati (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2026)
Children with special needs often have difficulty understanding and applying clean and healthy living behaviors independently, including proper handwashing. This condition increases the risk of infectious diseases in both school and home environments. This community service activity aimed to improve children with special needs' six-step handwashing skills at SLB-C Tunagrahita YPPLB Makassar. The activity was conducted through health education, demonstrations, direct practice, and assistance using educational media such as posters, animated videos, hand sanitizer, and handwash. The participants included students, teachers, and parents. Evaluation was carried out through direct observation of participants’ ability to perform the six-step handwashing procedure according to WHO standards. The results showed that most participants were able to follow the demonstrations and practice proper handwashing independently. This activity effectively improved handwashing skills and supported the implementation of Clean and Healthy Living Behavior (PHBS) among children with special needs.